A gis-based tool for estimating soil loss in agricultural river basins - Maria Augusta Gonçalves Fujaco; Mariangela Garcia Praça Leite; Antônio Henrique Caldeira Jorge Neves (REM: International Engineering Journal)
Abstract Soil erosion is a major problem observed in terrestrial ecosystems. Monitoring and identifying potential areas for erosion becomes extremely important for the better management of these areas. The main aim of this study was to develop a Geographic Information System script tool based on the universal soil loss equation (USLE), which calculates soil loss in three large agricultural sub-basins. Algorithms were implemented in the graphical interface of ModelBuilder and later in Python programming language, thus allowing the creation of a specific script to calculate soil loss in an automatic way. The "USLE Paracatu Watershed" script was validated and proved to be effective in estimating erosion in the three sub-basins with an average processing time of half second per km2. This can be added via "ArcToolbox" toolbox in ArcGIS software, so that the user only has to add the variables of the USLE equation and the software will process the algorithms in an automatic way, generating the final map with the soil loss value (t/ha.year). The friendly interface of the script allows it to be used in any area, only requiring the user to enter the updated data of parameters that compose the equation.